Sosialisasi Strategi Produksi Pada Usaha Dagang Kue Pia Mr Jalan Dempo VI Kelurahan Sawah Lebar Rt 21 Bengkulu - Irwanto, Tito; Pratama, Meylan; Rasuma, Hafiz Agung; Rajaliu, Haqil; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2022)
This community service program was carried out on Jalan Dempo VI, Sawah Lebar Village, RT 21 Bengkulu, which is one of the villages located in the Ratu Agung sub-district. The process of making this journal is aimed at how the production management functions in the manufacture and sale of cakes in the PIA